Elastomers with C-O-Si bonds between polyester backbone and crosslinker
By developing a new elastomer with polyester backbone and using carbon-oxygen-silicon bond crosslinking, the existing polysiloxane elastomers have been solved, and the problems of low organic content and poor environmental friendliness have been achieved, achieving higher organic content and better washing resistance and environmental friendliness.
Patent Information
- Application Number
- CN202380063183.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-05
- Publication Date
- 2025-04-08
AI Technical Summary
Although existing polysiloxane elastomers can thicken and provide sensory properties in cosmetics, their organic content is low and not easy to degrade, affecting environmental friendliness. In addition, the washing resistance of cosmetics is insufficient, resulting in a short stay on the skin.
A new type of elastomer was developed with a polyester backbone that was free of siloxane bonds and crosslinked by carbon-oxygen-silica bonds. The elastomer is formed by hydrosilylation reaction of the main chain polymer with the crosslinking agent, which has a higher organic content and a lower hydrolysis stability, improving its environmental friendliness and wash resistance.
The new elastomer provides similar thickening and organoleptic properties to polysiloxane elastomers in cosmetics, while having higher organic content and better environmental friendliness. Its durability and washability on the skin have also been significantly improved.
Smart Images

Figure BDA0005292377600000111 
Figure BDA0005292377600000112 
Figure BDA0005292377600000131
Abstract
Description
Technical Field
[0001] The present invention relates to elastomers and gels and pastes containing the elastomers.
[0002] introduction
[0003] Silicone elastomeric materials are needed in the cosmetic industry to thicken carrier fluids while imparting desirable sensory properties to cosmetics. Silicone elastomers are cross-linked gel materials that impart the smooth, dry, powdery feel desired in many cosmetics while also thickening the carrier fluid. Silicone elastomers contain a polysiloxane backbone cross-linked by a polysiloxane cross-linking agent.
[0004] It is of interest to identify elastomeric materials that can provide similar sensory and thickening properties to polysiloxane elastomers but also have a higher organic content. Increasing the organic content can increase compatibility with non-aqueous solvents, which may be expected to increase the versatility of formulations in which the elastomer is useful. In this regard, it is desirable to identify elastomers that have the thickening and sensory properties of polysiloxane elastomeric materials but contain a backbone that does not contain silicone.
[0005] It is also desirable to improve the environmentally friendly properties of elastomers by, for example, reducing the hydrolytic stability of the elastomer so that it can more easily decompose over time. Degradability, especially between the backbone polymer and the crosslinker, can promote polymer degradation over time.
[0006] Cosmetics that rely on silicone elastomers for thickening and sensory properties can further benefit from wash-off resistance, allowing them to stay in place for a longer period of time once applied to the skin. One way to help increase the durability of cosmetics is to identify elastomer gels that can be processed into pastes with desirable wash-off resistance (wear-off) sensory properties.
[0007] It is desirable to identify an elastomer that provides similar thickening and sensory properties as silicone elastomers, but has a non-silicone backbone polymer linked to the crosslinker via bonds that are less hydrolytically stable than carbon-oxygen-carbon bonds (COC), and has wash durability that is at least as good as or better than silicone elastomers. Summary of the invention
[0008] The present invention provides a solution to the problem of identifying elastomers that provide similar thickening and sensory properties as silicone elastomers, but have a non-silicone backbone polymer connected to the crosslinker through bonds that are less hydrolytically stable than carbon-oxygen-carbon (COC) bonds, and have wash durability that is at least as good as or better than silicone elastomers.
[0009] The present invention is the result of the discovery of how to prepare elastomers having a polyester backbone that is free of siloxane bonds and that is crosslinked by carbon-oxygen-silicon bonds (CO-Si) that are less hydrolytically stable than COC bonds, which can produce elastomers having the aforementioned desirable properties.
[0010] In a first aspect, the present invention is a composition comprising an elastomer characterized by having a polyester backbone crosslinked with a crosslinking agent and having carbon-oxygen-silicon bonds between the ester groups and the crosslinking agent.
[0011] In a second aspect, the present invention is a method for preparing a composition according to any one of the preceding claims, the method comprising preparing an elastomer by the following steps: (a) providing a backbone polymer and a crosslinker material, the backbone polymer having at least two terminal unsaturated carbon-carbon bonds separated from any polyester groups by carbon-oxygen-silicon bonds, and the crosslinker material containing a plurality of hydrosilyl groups, provided that at least one of the backbone polymer or the crosslinker has an average unsaturated carbon-carbon bond functionality greater than two and / or the crosslinker has an average hydrosilyl functionality greater than two; and (b) crosslinking the backbone polymer and the crosslinker material by hydrosilylation addition between the unsaturated carbon-carbon bonds of the backbone polymer and the hydrosilyl groups of the crosslinker material to form an elastomer.
[0012] The elastomers of the present invention can be used as additives for cosmetics to achieve the desired sensory properties of the cosmetics, in particular to achieve a smooth, dry, powdery feel while achieving long-lasting properties with respect to wash fastness. DETAILED DESCRIPTION
[0013] When a test method number is not used to indicate a date, the test method refers to the most current test method as of the priority date of this document. Reference to a test method includes reference to both the testing association and the test method number. The following test method abbreviations and designations apply herein: ASTM refers to ASTM International methods; END refers to European standards; DIN refers to the German Institute for Standardization; ISO refers to the International Organization for Standardization; and UL refers to Underwriters Laboratories.
[0014] Products identified by their trade names refer to compositions available under those trade names on the priority date of this document.
[0015] "Plurality" means two or more. "And / or" means "and, or as an alternative." Unless otherwise indicated, all ranges are inclusive.
[0016] The "unsaturated carbon-carbon bond" may be a carbon-carbon triple bond, or preferably a carbon-carbon double bond (C=C).
[0017] In one aspect, the present invention is a composition comprising an elastomer. The composition may be an elastomer or may be a combination of components comprising an elastomer. Desirably, the composition is a solvent swollen gel comprising an elastomer swollen with a solvent (typically a non-aqueous solvent) (i.e., a solvent swollen elastomer). The solvent swollen elastomer may be in a granular form in a solvent (particularly a non-aqueous solvent) to form a paste. A paste may be formed by subjecting the solvent swollen elastomer gel to shear (typically in excess solvent) to crush the elastomer gel into particles. The degree of shear may determine the particle size of the elastomer gel in the paste. Typically, the finer the particle size, the smoother (less granular) the resulting paste feels, so finer particle sizes are required in applications such as cosmetics applied to the skin.
[0018] The solvent is desirably a non-aqueous solvent and may be a non-polar solvent. The solvent may be, for example, any one or any combination of fluids selected from the group consisting of hydrocarbons, ethers, esters, alcohols, and silicone fluids. Examples of suitable hydrocarbon fluids include alfalkanes, squalanes, isohexadecanes, undecanes, tridecanes, and isododecanes. Examples of suitable ether fluids include those sold under the name CETIOL TM OE (CETIOL is a trademark of Cognis IP Management GMBH) materials sold from BASF, ethyl 3-(2,4-dimethyl-1,3-dioxolan-2-yl) propionate, ethyl glyceryl acetal levulinate, ethyl phenethyl acetal, and isopropylglycerol cocoate. Examples of suitable ester fluids include isodecyl neopentanoate, isostearyl neopentanoate, isononyl isononanoate, ethyl acetate, capric triglyceride, caprylic triglyceride, triheptanoin, triisostearin, diisopropyl acetate, diisopropyl adipate, diisobutyl adipate, diethylhexyl adipate, n-propyl acetate, isobutyl acetate, n-butyl acetate, trimethylolpropane trioctanoate, trimethylolpropane tricaprate, dipentaerythritol hexa C5-9 ester, C12-15 alkyl benzoate, triisooctano ... glyceryl stearate, neopentyl glycol diheptanoate, diheptyl succinate, heptyl undecylenate, propylene glycol dibenzoate, dipropylene glycol dibenzoate, ethylhexyl palmitate, ethylhexyl stearate, isopropyl laurate, hexyl laurate, isopropyl myristate, isopropyl palmitate, n-butyl stearate, propylene glycol dicaprylate, propylene glycol dicaprate, coco caprylate, coco caprate, ethylhexyl cocoate, oleyl erucate, propylheptyl caprylate, decyl oleate, hexyl decyl stearate, and propylene glycol laurate. Examples of suitable silicone fluids include cyclic siloxanes such as cyclotetrasiloxane, such as DOWSIL TM244 fluid (DOWSIL is a trademark of The Dow Chemical Company); cyclopentasiloxane, such as DOWSIL TM 245 fluid available; or cyclohexasiloxane, such as DOWSIL TM 246 fluid available; linear and branched alkyl and aryl siloxanes, such as octyl polymethicone, such as DOWSIL TM FZ-3196 available; and linear dimethyl siloxanes, such as DOWSIL TM 200 fluid available; and phenyl trimethicone, such as DOWSIL TM 556 fluid available. If the solvent includes a silicone fluid, it may also include an additional solvent. The solvent may also be free of silicone.
[0019] The solvent may be a "high volatility" solvent selected from the group consisting of isododecane (boiling point 210°C at 101 MPa), farnesane (boiling point 252°C at 101 MPa), undecane (boiling point 195°C at 101 MPa), n-dodecane (boiling point 216°C at 101 MPa) and tridecane (boiling point 234°C at 101 MPa). These solvents form gels that can be converted into pastes having higher washing durability than pastes made from conventional pure silicone elastomers.
[0020] The solvent concentration in the solvent-swollen elastomer composition is desirably 25 weight percent (wt %) or more, preferably 30 wt % or more, 35 wt % or more, 40 wt % or more, 45 wt % or more, 50 wt % or more, 55 wt % or more, 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, even 80 wt % or more, while typically 85 wt % or less, 80 wt % or less, 75 wt % or less, 70 wt % or less, 65 wt % or less, 60 wt % or less, 55 wt % or less, 50 wt % or less, 45 wt % or less, 40 wt % or less, 35 wt % or less, based on the combined weight of the solvent and the elastomer.
[0021] Elastomers are crosslinked polymers comprising a backbone polymer ("backbone") interconnected with other backbone polymers by a crosslinker polymer ("crosslinker"). Desirably, each backbone polymer has at least three bonds to the crosslinker and / or each crosslinker has at least three bonds to the backbone polymer.
[0022] The backbone is a polyester, which is a molecule comprising multiple polyester groups. The backbone polyester may not contain siloxane (Si-O-Si) bonds between the ester groups. The elastomer may or may not contain a polysaccharide component.
[0023] The crosslinking agent is bonded to the backbone through a linking group, which includes and can be a carbon-oxygen-silicon (CO-Si) bond. The linking group is present between the ester group in the backbone and the crosslinking agent. The crosslinking agent is typically a polysiloxane, which is a molecule containing multiple Si-O-Si bonds.
[0024] Desirably, the elastomer comprises a backbone containing no Si-O-Si bonds and containing ester bonds and a crosslinker containing Si-O-Si bonds. In such an elastomer, the backbone is clearly a component containing no Si-O-Si bonds between ester groups, and the crosslinker is clearly a component containing Si-O-Si bonds between CO-Si bonds. Desirably, at least one CO-Si bond is present between any polyester and any Si-O-Si bond in the elastomer.
[0025] The backbone component of the elastomer may comprise or consist of segments having any one or any combination of more than one of the chemical structures (I), (II) and (III), wherein the unbonded bonds represented by "--" are connected to the crosslinking agent:
[0026] -CH(CH 3 )-SiR 2 O-[(CH 2 ) m OC(O)CH 2 (CH 2 ) n CH 2 C(O)O-] o (CH 2 ) m -OSiR 2 -CH(CH 3 )-- (I)
[0027] C(R)[CH 2 OX] 3 (II)
[0028] CH 3 CH(OX)CH 2 CH 2 OX (III) where:
[0029] R is independently selected from the alkyl group with one to 8 carbon atom when occurring at every turn, and can be all identical or can be different from each other.The alkyl group can have one or more, two or more, three or more, four or more, 5 or more, 6 or more, even 7 or more carbon atoms, and contains 8 or less and can contain 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, even 2 or less carbon atoms usually at the same time.Expectedly, the R group is selected from the group consisting of methyl, ethyl, propyl group and phenyl group.
[0030] X is independently selected at each occurrence from -H, -C(O)-(CH 2 ) 4 C(O)OH and -C(O)-(CH 2 ) 4 C(O)OSiR 2 -CH 2 CH 2 --, wherein R is as described above, provided that at least two X groups are -C(O)-(CH 2 ) 4 C(O)OSiR 2 -CH 2 CH 2 --Group.
[0031] The subscript m independently at each occurrence has an average value ranging from one to eight, and preferably has a value of 2 or greater and can have a value of 3 or greater, 4 or greater, 5 or greater, 6 or greater, or even 7 or greater, while typically having a value of 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less. Desirably, the subscript m is 2 at each occurrence.
[0032] The subscript n has an average value ranging from 2 to 5. The subscript n can have a value of 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, or even 40 or more, while typically having a value of 50 or less, 45 or less, 40 or less, 35 or less, 31 or less, 25 or less, 20 or less, 10 or less, or even 5 or less.
[0033] Subscript o has an average value ranging from 2 to 10. Subscript o can have a value of 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, or even 9 or more, while typically having a value of 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less.
[0034] The crosslinker segment of the elastomer may comprise or consist of any one or any combination of more than one of the following segments (IV) and (V): wherein "--" corresponds to a bond attached to a carbon atom of the backbone chain, and may correspond to the same bond represented by "--" in structures (I), (II) and (III):
[0035] (--(CH 3 ) 2 SiO 1 / 2 ) 2 ((CH 3 )SiO 2 / 2 ) b (IV)
[0036] ((CH 3 ) 3 SiO 1 / 2 ) 2 ((CH 3 ) 2 SiO 2 / 2 ) c (--(CH 3 )SiO 2 / 2 ) d (V)
[0037] in
[0038] The subscript b corresponds to the ((CH 3 )SiO 2 / 2 ) groups and typically has a value of 5 or more, and may have a value of 10 or more, 15 or more, or even 16 or more, while at the same time typically has a value of 30 or less, and may be 25 or less, 20 or less, or even 17 or less;
[0039] The subscript c corresponds to the ((CH 3 ) 2 SiO 2 / 2 ) groups and typically has a value of 2 or more and can be 3 or more, 5 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, or even 90 or more, while at the same time typically is 100 or less, and can be 95 or less, 92 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 25 or less, 20 or less, 10 or less, or even 5 or less; and
[0040] The subscript d corresponds to the (--(CH3 )SiO 2 / 2 ) groups and typically has a value of 2 or more, and can be 3 or more, 4 or more, 5 or more, or even 6 or more, while at the same time typically has a value of 10 or less, and can be 9 or less, 8 or less, 7 or less, or even 6 or less.
[0041] In a second aspect, the present invention is a method for preparing a composition of the first aspect of the present invention. The method comprises preparing the elastomer of the first aspect by the following steps: (a) providing a backbone polymer and a crosslinker material, the backbone polymer having at least two terminal unsaturated carbon-carbon bonds separated from any polyester groups by carbon-oxygen-silicon bonds, the crosslinker material containing a plurality of hydrosilyl groups, provided that at least one of the backbone polymer or the crosslinker has an average unsaturated carbon-carbon bond functionality greater than two and / or the crosslinker has an average hydrosilyl functionality greater than two; and (b) crosslinking the backbone polymer and the crosslinker material by hydrosilylation addition between the unsaturated carbon-carbon bonds of the backbone polymer and the hydrosilyl groups of the crosslinker material to form an elastomer. The "functionality" of the backbone polymer refers to the terminal unsaturated carbon-carbon bonds, and the "functionality" of the crosslinker material refers to the hydrosilyl groups.
[0042] The backbone polymer is desirably an organosilyl-functional polyester comprising at least two organosilyl-functional groups, each having at least one terminal unsaturated carbon-carbon bond. "Organosilyl-functional" refers to a polyester having at least one -SiR 3 Group, preferably multiple SiR 3 A group wherein each R is independently selected from a hydrocarbyl group, including an alkyl group, an alkenyl group, and an aryl group.
[0043] Examples of suitable organosilyl-functional polyesters include any one or any combination of more than one of the organosilyl-functional polyesters having the average chemical structure (VI), (VII), or (VIII):
[0044] CH 2 =CH-SiR 2 O-[(CH 2 ) m OC(O)CH 2 (CH 2 ) n CH 2 C(O)O-] o (CH 2 ) m -OSiR 2 -CH=CH 2 (VI)
[0045] C(R)[CH 2 OX] 3 (VII)
[0046] CH 3 CH(OX)CH 2 CH 2 OX (VIII) where:
[0047] R is independently selected from the alkyl group with one to 8 carbon atom when occurring at every turn, and can be all identical or can be different from each other.The alkyl group can have one or more, two or more, three or more, four or more, 5 or more, 6 or more, even 7 or more carbon atoms, and contains 8 or less and can contain 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, even 2 or less carbon atoms usually at the same time.Expectedly, the R group is selected from the group consisting of methyl, ethyl, propyl group and phenyl group.
[0048] X is independently selected at each occurrence from -H, -C(O)-(CH 2 ) 4 C(O)OH and -C(O)-(CH 2 ) 4 C(O)OSiR 2 -CH=CH 2 , wherein R is as described above, provided that at least two X groups are -C(O)-(CH 2 ) 4 C(O)OSiR 2 -CH=CH 2 Group.
[0049] The subscript m independently at each occurrence has an average value ranging from one to eight, and preferably has a value of 2 or greater and can have a value of 3 or greater, 4 or greater, 5 or greater, 6 or greater, or even 7 or greater, while typically having a value of 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less. Desirably, the subscript m is 2 at each occurrence.
[0050] The subscript n has an average value ranging from 2 to 5. The subscript n can have a value of 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, or even 40 or more, while typically having a value of 50 or less, 45 or less, 40 or less, 35 or less, 31 or less, 25 or less, 20 or less, 10 or less, or even 5 or less.
[0051] Subscript o has an average value ranging from 2 to 10. Subscript o can have a value of 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, or even 9 or more, while typically having a value of 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less.
[0052] The organosilyl functional polyester desirably has an Mw in the range of 1000 to 5000 grams per mole (g / mol), preferably 1200 to 2500, and may be in the range of 1400 to 2300. The molecular weight of the organosilyl functional polyester was determined using gel permeation chromatography using a Waters 2695 separation module equipped with a vacuum degasser and a Waters 2410 differential refractometer. Two (300 mm x 7.5 mm) Polymer Laboratories PLgel 5 micron Mixed-C columns (molecular weight separation range of 200 to 2,000,000) were used, preceded by a PLgel 5 micron guard column (50 mm x 7.5 mm). Certified grade tetrahydrofuran (THF) flowing at 1.0 ml / min was used for the polyester samples and toluene was used for the crosslinker samples as the eluents while the columns and detectors were maintained at 35°C. Polyester samples were prepared in THF at a concentration of about 0.15% by volume and crosslinker samples were prepared in toluene and allowed to solvate for two hours with occasional shaking, then filtered through a 0.45 micron polytetrafluoroethylene syringe filter before analysis. 100 microliters of sample were injected for analysis, and data were then collected for 30 minutes. Data were collected and analyzed using ThermoLabsystems Atlas chromatography software and Polymer Laboratories Cirrus GPC software. Molecular weight averages are relative to a calibration curve (third order) created using polystyrene standards covering a molecular weight range of 580 to 2,750,000.
[0053] The crosslinker material is a hydrosilyl functional (SiH functional) compound, preferably a SiH functional polysiloxane. The crosslinker material contains at least two SiH functional groups. The SiH functional polysiloxane can be branched or linear, but is preferably linear. The SiH functional polysiloxane can have one or more than one terminal SiH group without side SiH groups, one or more than one side SiH group without terminal SiH groups, or a combination of one or more terminal SiH groups and one or more side SiH groups.
[0054] Desirably, the SiH functional polysiloxane is linear and is one compound or any combination of more than one compounds selected from those having the following average chemical formula:
[0055] (R' 3 SiO 1 / 2 ) 2 (R' 2 SiO 2 / 2 ) b
[0056] in:
[0057] R' at each occurrence is independently selected from the group consisting of hydrogen and R groups, wherein R is as described above, provided that at least two R' groups are hydrogen;
[0058] Subscript b is the number of molecules (R' 2 SiO 2 / 2 ) groups and typically has a value of 5 or more, and can be 10 or more, 15 or more, 20 or more, 30 or more, 50 or more, 70 or more, or even 90 or more, while at the same time typically is 120 or less, or even 100 or less, and can be 70 or less, 50 or less, 30 or less, 20 or less, 15 or less, or even 10 or less.
[0059] Examples of suitable hydrosilyl functional polysiloxanes include those having the following average molecular formula:
[0060] (H(CH 3 ) 2 SiO 1 / 2 ) 2 ((CH 3 )SiO 2 / 2 ) 20 ,
[0061] ((CH 3 ) 3 SiO 1 / 2 ) 2 ((CH 3 ) 2 SiO 2 / 2 ) 25 (H(CH 3 )SiO 2 / 2 ) 6 ,
[0062] ((CH 3 ) 3 SiO 1 / 2 ) 2 ((CH 3 ) 2 SiO 2 / 2 ) 92 (H(CH 3 )SiO 2 / 2 )6 ,and
[0063] ((CH 3 ) 3 SiO 1 / 2 ) 2 ((CH 3 ) 2 SiO 2 / 2 ) 3.3 (H(CH 3 )SiO 2 / 2 ) 6 .
[0064] When present, the hydrosilyl-functional polysiloxane is desirably present in a concentration sufficient to provide a molar ratio of SiH functionality from the crosslinker material to unsaturated carbon-carbon bonds from the backbone polymer of 0.7 or greater, preferably 0.90 or greater, while typically 1.5 or less, preferably 1.0 or less, even more preferably 0.95 or less.
[0065] The main chain polymer and the crosslinker material are crosslinked by hydrosilylation addition between the unsaturated carbon-carbon bonds of the main chain polymer and the hydrosilyl groups of the crosslinker material to form the elastomer of the first aspect of the present invention.
[0066] Typically, it is desirable to conduct the hydrosilylation reaction in the presence of a hydrosilylation catalyst. Typically, the hydrosilylation catalyst is any one or any combination of more than one platinum-based hydrosilylation catalysts. Platinum-based hydrosilylation catalysts include compounds and complexes such as platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Karstedt's catalyst), H 2 PtCl 6 , di-μ.-carbonyldi-.π.-cyclopentadienyldininickel, platinum-carbonyl complexes, platinum-divinyltetramethyldisiloxane complexes, platinum cyclovinylmethylsiloxane complexes, platinum acetylacetonate (acac), platinum black, platinum compounds (such as chloroplatinic acid, chloroplatinic acid hexahydrate, reaction products of chloroplatinic acid and monohydric alcohols, bis(ethyl acetoacetate) platinum, bis(acetylacetonate) platinum, platinum dichloride) and complexes of platinum compounds with olefins or low molecular weight organopolysiloxanes or platinum compounds microencapsulated in a matrix or core-shell structure. The hydrosilylation catalyst may be part of a solution comprising complexes of platinum with low molecular weight organopolysiloxanes, including complexes of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane with platinum. These complexes may be microencapsulated in a resin matrix. The catalyst may be a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane with platinum.
[0067] The concentration of the platinum-based hydrosilylation catalyst is typically 5 million weight-parts per million (ppm) or more, preferably 10 ppm or more, and can be 25 ppm or more, 50 ppm or more, or even 75 ppm or more, based on the combined weight of the cross-linker material and the backbone polymer. It is typically 500 ppm or less, 400 ppm or less, 300 ppm or less, 200 ppm or less, and preferably 100 ppm or less, and can be 90 ppm or less, 80 ppm or less, 70 ppm or less, 60 ppm or less, or even 50 ppm or less.
[0068] It is desirable to conduct the hydrosilylation reaction in a non-aqueous solvent to produce a solvent swollen elastomer. Examples of suitable solvents include the above solvents, including non-polar solvents. Desirably, when the solvent is a polysiloxane and the organosilyl functional polyester contains more than 2 terminal carbon-carbon double bonds, the molecular weight of the crosslinking agent is less than 7500, and may have a molecular weight of 7400 or less, and preferably has a molecular weight of 2400 or less, even 2390 or less, more preferably 1400 or less, even 1390 or less. The molecular weight of the crosslinking agent material is determined using the method described above for the organosilyl functional polyester.
[0069] The method may include forming the solvent swollen elastomer and then subjecting the solvent swollen elastomer to shear to break the solvent swollen elastomer into particulate form to produce a paste. Optionally, a non-aqueous solvent may be added to the solvent swollen elastomer before, during and / or after subjecting the solvent swollen elastomer to shear. In the widest range, there is no limitation on how the solvent swollen elastomer is subjected to shear. For example, mixing the solvent swollen elastomer with a mixing blade may apply shear to break the solvent swollen elastomer into particulate form. The degree of shear may determine the particle size of the elastomer gel in the paste. Generally, the finer the particle size, the smoother (less granular) the resulting paste feels, so finer particle sizes are desired in applications such as cosmetics applied to the skin.
[0070] Example
[0071] The backbone polymer was prepared according to the following method, and then the samples of the Examples (Ex) and Comparative Examples (CEx) of the present invention were prepared according to the following subsequent procedures.
[0072] Preparation of organosilyl functional polyester backbone polymers
[0073] Table 1 lists the components used to prepare the following examples.
[0074] Table 1
[0075]
[0076] PRIPLAST is a trademark of Croda International PLC. DESMOPHEN is a trademark of Covestro Intellectual Property GMBH.
[0077] Table 2 provides the concentrations (in grams) of the polyester polyol, catalyst, and divinyldisilazane used to prepare each organosilyl-functional polyester, as well as the reaction time (in hours) and reaction temperature (° C.) for each of the organosilyl-functional polyesters 1 to 3. Additionally, Table 2 lists the average mole percent (mol %) OH substitution (silylation) relative to the number of OH moles in the polyester polyol, the wt % vinyl groups per molecule based on the weight of the organosilyl-functional polyester, and the average number of vinyl groups per organosilyl-functional polyester molecule.
[0078] Table 2
[0079]
[0080] The polyester polyol, divinyldisilazane and catalyst are added to a 500 milliliters (mL) round bottom flask. A polytetrafluoroethylene stirring rod is added, and the flask and contents are purged with nitrogen and sealed with a septum. The contents are heated to the reaction temperature using a hot plate while stirring the reaction time. The mixture is cooled to 23° C. and residual divinyldisilazane is removed under vacuum (1.3 kPa) and 130° C. for 2 hours to obtain the resulting organosilyl functional polyester.
[0081] Through protons ( 1 H) Characterization of the obtained organosilyl functional polyester by nuclear magnetic resonance (NMR) spectroscopy. A 10 mg sample of the organosilyl functional polyester was dissolved in 0.6 ml of deuterated benzene (d6-benzene) and spectroscopy was performed using a 400 MHz Varian 1HNMR spectrometer analysis. A 5 second acquisition time and a 15 second relaxation delay time were used. 16 scans were collected and averaged to obtain the resulting spectrum. The resulting spectrum was referenced to benzene at δ7.16 ppm. The regions of interest in the spectrum are: the vinyl region ("V") integrated from δ5.6-6.5 ppm; the methylene region adjacent to the hydroxyl group ("O") is integrated at δ4.2-4.3 ppm to determine hydroxyl substitution. δ2.1-2.3 ppm illustrates the exclusion of methylene adjacent to the ester region ("E") and the methyl region at δ0.15-0.3 ppm illustrates silanization ("S"). The integral is set based on the number of repeating units along the polyester polymer backbone: for polyester 1, region "E" is normalized to 16; for polyester 2, region "E" is normalized to 30; and for polyester 3, region "E" is normalized to 24. The mol% OH substitution is calculated as the integral of the region corresponding to "V" divided by the theoretical vinyl integral based on OH for each polyester polyol. The theoretical vinyl integrals for polyester 1 and polyester 2 are 6, and polyester 3 is 16.5. The following calculations were used:
[0082] Mol% OH substitution = [(V) / (OH per polyester polymer)*3]*100%
[0083] Wt% Vinyl = [Molecular weight of vinyl groups] * [mol% OH substitution] / [MW / OH of polyester], where MW / OH of polyester 1 and polyester 2 is 1000, and polyester 3 is 260.
[0084] Vinyl groups per polyester = [Mol % OH substitution] * [OH per polyester], where for polyester 1 and polyester 2 the OH per polyester is 2, and for polyester 3 the OH per polyester is 5.5.
[0085] The organosilyl functional polyester 1 has an average chemical structure:
[0086] CH 2 =CH-Si(CH 3 ) 2 O[(CH 2 ) 2 OC(O)CH 2 (CH 2 ) 31 CH 2 C(O)O-] 3.9 (CH 2 ) 2 OSi(CH 3 ) 2 -CH=CH 2
[0087] The organosilyl functional polyester 2 has an average chemical structure:
[0088] CH 2 =CH-Si(CH 3 ) 2 O[(CH 2 ) 2 OC(O)CH 2 (CH 2 ) 13 CH 2 C(O)O-] 7.5 (CH 2 ) 2 OSi(CH 3 ) 2 -CH=CH 2
[0089] The organosilyl functional polyester 3 may have a combination of structures, but is contemplated to include materials having the following average chemical structure:
[0090]
[0091] Preparation of Ex and CEx
[0092] Table 3 lists the components used to prepare the following Examples (Ex) and Comparative Examples (CEx).
[0093] Table 3
[0094]
[0095] CETIOL is a trademark of Corning Intellectual Property Management, Inc. CRODAMOL is a trademark of Croda Corporation. CERAPHYL is a trademark of ISP Investments, Inc. DOWSIL is a trademark of The Dow Chemical Company. SYL-OFF is a trademark of Dow Silicones Corporation.
[0096] Elastomer samples were prepared using the following hydrosilylation procedure. The identity and concentration in grams ("[g]") of each component are in Table 4. The organosilyl functional polyester ("OFP"), crosslinker, and solvent were combined in a 20 ml glass scintillation vial equipped with a magnetic stir bar and the components were stirred at 250 rpm to form a mixture. The mixture was heated to the reaction temperature shown in Table 4 and then a hydrosilylation catalyst was added at the concentration shown in Table 4 in parts by weight per million parts by weight of the mixture. The mixture was maintained at the reaction temperature for 3 hours and then allowed to cool to 25°C.
[0097] Successful formation of the solvent swollen elastomer (Rxn Success = Y) is evident if the reaction product flows one centimeter or less in the scintillation vial when inverted for one minute.
[0098] Table 4 reports the identity of each component, the amount of each component, the molar ratio of hydrosilyl groups to carbon-carbon double bonds (SiH:C=C), the reaction temperature (Temp), and whether successful formation of a solvent-swollen elastomer occurred.
[0099] CEx A discloses that when the backbone polymer has an average of two unsaturated carbon-carbon bonds and the crosslinker material has an average of two SiH groups, the reaction fails to cure to an elastomer. However, other examples disclose that as long as either the backbone polymer or the crosslinker material has an average of more than two functional groups, the other can have two functional groups and the reaction will form an elastomer.
[0100] Exs 26-39 and CEx B and CEx C illustrate that when using polysiloxane solvents with organosilyl functional polyesters having more than 2 terminal carbon-carbon double bonds, it is desirable to use a crosslinker having a molecular weight below 7400.
[0101] Table 4
[0102]
[0103] Paste samples
[0104] Pastes were prepared by shearing the above example materials using a Waring 7012 mixer. For Paste 1 and Paste 2, solvent was added gradually while shearing was applied. Table 5 identifies exemplary compositions for preparing pastes and identifies which example materials were used, how much was added (in grams), which solvent was added and how much was added (in grams), the resulting solids concentration in wt% relative to the weight of the paste, and the final paste viscosity in millipascals * seconds (mPa * s). Paste viscosity was measured using a Brookfield DV-IIPlus Pro programmable viscometer with a lift stand spindle (S94) at 2.5 rpm and 25°C.
[0105] Table 5
[0106]
[0107] Sensory Feeling
[0108] Characterize the paste samples and the TM 9041 (reference 1) and DOWSIL TM3901 (Reference 2) Sensory perception of two commercially available polydimethylsiloxane materials obtained from The Dow Chemical Company. Reference 1 was used as the silicone material having desirable sensory perception characteristics. Reference 2 was a silicone material having undesirable sensory perception characteristics.
[0109] The sensory sensory evaluation was performed using a panel of 10 trained sensory evaluators. Prior to the evaluation, the panelists washed their forearms, hands and fingers with a 4.3% active sodium lauryl ether sulfate aqueous solution, then rinsed with distilled water and dried with a paper towel. For the evaluation, each panelist applied 50 mg of the sample material to the inside of their forearm, making circular motions at a rate of 2 wipes per second, up to a maximum of 120 wipes. The panelists characterized the skin sensory parameters mentioned below on a scale of 1-5, with 5 being the most likely parameter descriptor and 1 being the least likely parameter descriptor. A final value was assigned to each sample, which was the average of each parameter value of the 10 trained sensory evaluators. The parameters and descriptors are:
[0110]
[0111] For a "smooth, dry, powdery feel", it is desirable that the sample have a smoothness value greater than 3, a powderiness value greater than 2, and a wetness value less than 3. Table 6 provides the sensory evaluation results of Pastes 1 to 4, Reference 1, and Reference 2. The results show that, similar to the standard silicone material of Reference 1 and in contrast to Reference 2, the paste of the present invention successfully achieves the desired "smooth, dry, powdery feel".
[0112] Table 6
[0113] sample Smoothness Powder Greasy Adhesion humidity Reference 1 3.8 3.0 2.3 1.4 1.7 Paste 1 3.9 2.4 3.2 2.7 2.3 Paste 3 4.1 2.5 2.8 1.8 2.1 Paste 4 3.9 2.4 3.2 2.2 1.8 Reference 2 4.8 1.5 3.6 1.7 4.7
[0114] Durability
[0115] The durability of the paste was evaluated according to the following procedure. 8 g of the sample paste was added to a dental cup, followed by 2 g of Skolar Glare TM The samples were prepared using purple SG-7661E pigment (from CQV Ltd., Skolar Glare is a trademark of CQV Ltd.). Mixing was performed using a FlackTek DAC 150 speed mixer at 2000 rpm for 20 seconds. 0.3 g of the resulting mixture was applied to a 4.75 cm x 5 cm collagen-coated microscope slide. The coated samples were allowed to dry at 25°C for 24 hours. Using a wet fingertip, 0.07 g of DIAL TMA solution of dishwashing liquid (Henkel Corporation) in 0.07g water was applied to the coated slide for 20 seconds to wash the coated slide. A digital image of the slide was taken after washing and analyzed using Image J software to determine the area of the slide retaining the coating. The remaining coating area is reported as the percentage of the initial coating area, and it is the durability percentage of the sample. For durability, a higher value is more ideal. Table 7 reports the durability percentage of the sample.
[0116] Table 7
[0117] sample Durability % Reference 1 0 Paste 1 100 Paste 2 63 Paste 3 90 Paste 4 70 Reference 2 25
[0118] The data in Table 7 show that the paste of the present invention has greater durability than either silicone reference material. This is expected, the paste has a greater likelihood of remaining on the skin and providing a desirable sensory feel even after washing.
[0119] Solvent compatibility
[0120] The solvent compatibility of the samples was evaluated by combining 7.5 g of the sample and 2.5 g of the specified solvent (see Table 8) in a dental cup, and then mixed at 2300 rpm for 30 seconds using a FlackTek DAC 150 speed mixer. The material was transferred to a 20 ml clear glass vial and centrifuged at 3000 rpm for 20 minutes using an IEC K-type centrifuge. The samples were allowed to stand at 25°C for 24 hours, and then the samples were observed and characterized using the following scale, where lower values are better:
[0121] 1: Clear. The sample is not turbid and can be easily read through the mixture when the text is placed behind the vial containing the sample.
[0122] 2: Slightly Turbid. The sample is nearly clear with only very slight turbidity detectable and can still be easily read through the sample when the text is placed behind the vial containing the sample.
[0123] 3: Turbid. The sample is not clear and a person can detect but cannot read the text placed on the back of the vial containing the sample.
[0124] 4: Opaque. White solid. Light cannot pass through and cannot detect objects placed behind the vial.
[0125] 5: Incompatible. Sample phase separation.
[0126] The results for the sample materials are in Table 8. The data show that the pastes of the present invention generally have a broader solvent compatibility than either Ref 1 or Ref 2.
[0127] Table 8
[0128]
[0129] Hydrolytic stability
[0130] The relative hydrolytic stability of CO-Si bonds and CO-C bonds in organosilyl functional polyester 1 was evaluated. 15 mg of organosilyl functional polyester 1 was placed in a glass nuclear magnetic resonance (NMR) tube and 0.75 mL of deuterated chloroform (CDCl 3 ). Then 5 μl of a 10:1 mixture of deionized water / trifluoroacetic acid was added. Proton NMR spectra were collected immediately after addition of the water / acid mixture and at 5 and 25 hours. A 400 MHz Varian 1 The NMR spectra were collected on a H NMR spectrometer. A 5 second acquisition time and a 15 second relaxation delay time were used. 16 scans were collected and averaged to obtain the final spectrum for analysis. CDCl at δ 7.26 ppm 3 The mol% CO-Si hydrolysis and COC hydrolysis were determined at each time point. The dimethylvinylsilyl polyester peak (CO-Si(Me)) at δ 0.16-0.18 ppm was used to determine the mol% CO-Si hydrolysis and COC hydrolysis. 2 Vi) Integrate to determine the mol% CO-Si hydrolysis and the hydrolyzed dimethylvinylsilyl (HO-Si(Me) 2 Vi) from δ 0.21-0.22. By evaluating CDCl 3 The hydrolyzed dimethylvinylsilyl group (HO-Si(Me)) present at δ 0.21-0.22 2 Mol% CO-Si hydrolysis was determined by the growth of the resonance of α-D-H-Si (VI) relative to the resonance of the unhydrolyzed dimethylvinylsilyl polyester at δ 0.16-0.18 ppm. 3 The unhydrolyzed polyester (-CH 2 -OC(O)-C-) proton resonance relative to that in CDCl 3 The mol % COC hydrolysis was determined by integrating those resonances present in the hydrolysis composition (HO-C(O)-C) at 9-11 ppm.
[0131] The results in Table 9 show that the CO-C bond remains stable to hydrolysis, while the CO-Si bond is almost completely hydrolyzed within 25 hours. This confirms that the hydrolytic stability of the CO-Si bond is lower than that of the CO-C bond.
[0132] Table 9
[0133] Time (hours) Mol% CO-Si hydrolysis Mol% COC hydrolysis 0 4 0 5 41 0 25 85 0
Claims
1. A composition comprising an elastomer characterized by having a polyester backbone crosslinked with a crosslinking agent and having carbon-oxygen-silicon bonds between the ester groups and the crosslinking agent.
2. The composition of claim 1, wherein the polyester backbone is free of silicon-oxygen-silicon bonds.
3. A composition according to claim 1 or claim 2, wherein the crosslinking agent is a polysiloxane.
4. A composition according to any preceding claim wherein there is at least one carbon-oxygen-silicon bond between any polyester and any siloxane bond in the elastomer.
5. A composition according to any preceding claim, wherein each polyester backbone has at least three bonds to the crosslinker and / or each crosslinker has at least three bonds to the backbone polymer.
6. A composition according to any preceding claim wherein the elastomer is solvent swollen with a non-aqueous solvent.
7. The composition according to claim 5, wherein the elastomer is in the form of microparticles and the composition is in the form of a paste.
8. A method for preparing a composition according to any preceding claim, said method comprising preparing the elastomer by the following steps: a. providing a backbone polymer and a crosslinker material, wherein the backbone polymer has at least two terminal unsaturated carbon-carbon bonds separated from any polyester groups by carbon-oxygen-silicon bonds, and the crosslinker material contains a plurality of hydrosilyl groups, provided that at least one of the backbone polymer or the crosslinker has an average unsaturated carbon-carbon bond functionality greater than two and / or the crosslinker has an average hydrosilyl functionality greater than two; and b. crosslinking the backbone polymer and the crosslinker material to form an elastomer by hydrosilylation addition between the unsaturated carbon-carbon bonds of the backbone polymer and the hydrosilyl groups of the crosslinker material.
9. The method of claim 8, wherein the hydrosilylation reaction is carried out in a non-aqueous solvent and produces a solvent swollen elastomer, provided that if the non-aqueous solvent is a polysiloxane and the organosilyl-functional polyester contains more than two terminal carbon-carbon double bonds, the crosslinker has a weight average molecular weight less than [the molecular weight of crosslinker 3].
10. The method according to claim 9, further comprising: a. optionally adding additional non-aqueous solvent to the solvent-swollen elastomer; as well as b. subjecting the solvent swollen elastomer to shear so as to break the solvent swollen elastomer into particulate form to produce a paste.